Rapid improvement in organ procurement organization performance: Potential for change and impact of new leadership. Issue 12 (5th July 2020) - Niroomand, Elaheh; Mantero, Alejandro; Narasimman, Manasa; Delgado, Cindy; Goldberg, David
Abstract : Recently proposed rulemaking from Centers for Medicare and Medicaid Services would change how organ procurement organizations (OPOs) are evaluated. The proposals include using national inpatient death data to define a standardized denominator to calculate comparable donation rates among OPOs. Based on these objective metrics, OPOs not performing at a prespecified threshold will be required to rapidly improve performance to avoid decertification. We sought to determine whether rapid OPO improvement was possible based on objective donation metrics, and whether leadership change was associated with rapid improvement. We evaluated United Network for Organ Sharing and Centers for Disease Control and Prevention (CDC) data from 2011 to 2018, and measured donation rates using CDC data on inpatient deaths from causes consistent with donation, based on the location of deaths. During the two 4‐year cycles, we found that an OPO's ranking relative to other OPOs was fairly static, with more than 90% of the OPOs at risk of flagging at the end of each 4‐year cycle (2014, 2018) being in the bottom 75% of OPOs in the preceding 3 years. In multivariable logistic regression models, leadership changes were only statistically significantly associated with an improvement in OPO rankings during the 2011‐2014 cycle. These data demonstrate that rapid improvements in OPO performance are uncommon, and while leadership changes increase the odds of rapid improvement, they do not guarantee improvement. Abstract : Empirical data from 2011–2018 show that rapid improvements in OPO performance are uncommon and that leadership change favors but does not ensure rapid improvement.